Sosialisasi dan Pendampingan Kawasan Halal, Aman dan Sehat (KHAS) pada Kantin Universitas menuju Ekosistem Halal - Waska Warta; Iwan Satriyo Nugroho; Herayati; Desi Susilowati; Tinah Febrianti; Dian Rosinawati (JURPIKAT, 2026)
This community service program aims to realize the Halal, Safe, and Healthy (KHAS) Area in the Nusantara Islamic University (UNINUS) canteen towards a campus-based halal ecosystem. UNINUS as an Islamic university has the responsibility to guarantee halal consumption for 6,635 academics. The SIKOMIN canteen, managed by the SIMANTRA Cooperative with 14 tenants, is a strategic locus. The method used is Participatory Action Research (PAR) through the stages of problem identification, participatory planning, implementation, and reflection, which began with a Systematic Literature Review of 21 AI-assisted journals. Implementation includes socialization, training, and mentoring of tenants in the application of KHAS standards and the halal certification process with the support of the Salman Halal Center ITB. The results show an increase in halal literacy, changes in tenant behavior, and strengthening canteen governance. Institutionally, the program encourages the establishment of the UNINUS Halal Center and has the potential to develop a halal ecosystem in the surrounding community. This program is a model for developing a university-based halal area